The impact of electricity price on inflation in the Czech Republic : An ARDL analysis - Zhanbussinova, Zhanel (2024)
This research aims to find out whether or how electricity prices affect the Consumer Price index (CPI) in the Czech Republic. The impact can be significant because electricity has a certain weight in the CPI basket and the increase in its price is directly reflected in the higher cost of living. In addition, the transmission effect may lead to price increases in various electricity-dependent sectors, which will further increase CPI. In addition, rising electricity costs can affect production costs and consumer behaviour, which can lead to price adjustments and changes in the relative prices of goods and services within the CPI basket. This thesis adopts the Autoregressive Distributed Lag (ARDL) approach to cointegration originally formulated by Pesaran (19) and later refined by Pesaran, Shin, and Smith (20) with the bounds testing approach. While the final model shows progress in addressing autocorrelation and the overall significance, the impact of electricity prices on inflation remains unclear. Further exploration using alternative specifications, additional variables, or data transformations could be necessary to strengthen the model and confirm the electricity price effect.